Narrative skill and identification of values and countervalues in cartoons by Primary Education students - Oregui, Eider; Aierbe, Ana; Bermejo, Jesús (Anales de Psicología / Annals of Psychology, 2019)
This research analyses whether the structure (non-narrative or narrative) that characterizes cartoons affects the narrative skill and identification of values and countervalues, as opposed to personal (age, school year, gender and attention level) or contextual (school network and socioeconomic and cultural index of the school) factors of Primary Education students. 186 students participated in it, who have reported on the episode watched. The study has a quasi-experimental design with blended methodology (quantitative and qualitative). The results obtained through regression analysis confirm that the structure has a greater effect than the rest of the factors. We conclude that it is advisable to consider the structure of audio-visual content, not just the potential values or countervalues, both in future research and in designing and implementing interventions in formal and informal settings.